Dynamics of endogenous intoxication in experimental diabetes mellitus - Zaiats, Liubomyr; Fedorchenko, Yuliya; Zukow, Walery (Journal of Education, Health and Sport, 2022)
Background. Nowadays, diabetes mellitus is defined as one of the global medical and social problems and shows a growing tendency. The purpose of the study was to analyze the dynamics of endogenous intoxication in experimental diabetes mellitus. Materials and methods. The experiments were performed on 88 white male Wistar rats weighing 170-210 g. Animals were divided into three groups: 1 - intact; 2 - control; 3 - experimental with a model of diabetes mellitus, which was reproduced by intraperitoneal injection of streptozotocin by “Sigma" company (USA), diluted in 0.1 M citrate buffer with a pH of 4.5, at a rate of 60 mg/kg body weight. The control group of animals received an intraperitoneal injection with an equivalent dose of 0.1 M citrate buffer solution with a pH of 4.5. All studies were performed under thiopental-sodium anesthesia at a rate of 60 mg/kg body weight. To determine endogenous intoxication, blood sampling of middle mass molecules (MMM) was performed 14, 28, 42 and 70 days after the streptozotocin injection. Detection of MMM fractions was performed by spectrophotometer «SF46» at the wavelength of 254 nm (MMM254) and 280 nm (MMM280). The STATISTICA 10 program was used for statistical processing of the obtained results. Results. The conducted biochemical studies of blood serum showed that in animals with streptozotocin-induced diabetes mellitus there was an increase in the content of both MMM fractions compared to the similar indicators of the control group of animals at all stages of the experiment: in the 14 days increased by 32,9% - MMM254, by 12.7%- MMM280, in the 28 days increased by 44,3 % MMM254, by 34,0 % MMM 280, in the 42 days increased by 62,8 % MMM254, by 64,8 % MMM280, in 70 days increased by 76,1 % MMM254, by 81,1% MMM280. Conclusions. Streptozotocin-induced diabetes mellitus is accompanied by an increase in the level of endogenous intoxication which is manifested by an increase of both MMM fractions content in serum. The severity of endogenous intoxication depends on the duration of the endogenous factor.